(3x) + (x+60) = 180
4x + 60 = 180
Subtract 60 from both sides
4x = 120
Divide 4 from both sides
x = 30
Subtract 20 and 10. To get your answer
Answer:
(a) 3 - 2x - 2x² (b) -21
Step-by-step explanation:
given, y +2x² = 3 -2x
make y the subject:
y = 3 - 2x - 2x²
if y = f(x)
then
f(x) = 3 - 2x - 2x²
(b)<u> to find f(3) we need to replace x with 3:</u>
<u />
3 - 2(3) - 2*(3)²
-21
The difference between the two polynomials is 11x²3y³ - 4xy².
<h3>What is the Difference between the Polynomials?</h3>
The difference between two polynomials is the result you get by subtracting one from the other.
Thus:
= (4x²2y³ + 2xy² – 2y) – (–7x²y³ + 6xy² – 2y)
= 4x²2y³ + 2xy² – 2y + 7x²y³ - 6xy² + 2y
= 11x²3y³ - 4xy²
Learn more about polynomials on:
brainly.com/question/2833285
#SPJ1
2/3x + 4 = 7
-4 -4
4 cancels out.
2/3x = 3
x 3 x3
6/3 = 2x = 9
/2 /2
2 cancels out.
x = 9/2 = 4.5